Are chlamydial lipopolysaccachide-directed antibodies in seminal plasma or serum clinically significant during investigation of male infertility? - Eggert-Kruse, Waltraud; Weltin, Miriam; Strowitzki, Thomas (Urology, 2011)
Objectives - To analyze the clinical relevance of chlamydial serology in seminal plasma (SP)/serum for male fertility. - Methods - We determined the IgG, IgA, and IgM class antibodies to Chlamydia trachomatis with a lipopolysaccachide-directed standard enzyme-linked immunosorbent assay in the serum of 173 asymptomatic subfertile couples and in the same-day SP in a prospective study. The semen quality evaluation was done using aliquots of the same ejaculate (eg, sperm analysis, leukocytes, bacterial cultures, sperm functional capacity). The medical history, clinical examination, postcoital testing, and determination of subsequent fertility were also done. - Results - The antichlamydial antibodies of the 3 classes were significantly interrelated, and SP Chlamydia IgA antibodies were significantly associated with the findings in the serum. The evidence for previous or persistent chlamydial infection was significantly more frequent in the female partners of men with Chlamydia antibodies in the serum and/or Chlamydia IgA antibodies in the SP. The chlamydial serology results in the SP/serum were not associated with the sperm quality, leukocytes, semen culture findings, or sperm functional capacity. - Conclusions - The chlamydial serology results (ie, IgG, IgA, and IgM antibodies in SP/serum) determined using a lipopolysaccachide-directed enzyme-linked immunosorbent assay were not indicative of reduced sperm function or subsequent fertilizing capacity.
Gesehen am 06.04.2022